Digit Sucking Habit and Association with Dental Caries and Oral Hygiene Status of Children Aged 6 Months to 12 Years Resident in Semi-Urban Nigeria - Kolawole, Kikelomo Adebanke (PLoS One, 2016)
OBJECTIVES: Non-nutritive sucking (NNS) is a common behavior in childhood. The association between digit sucking, dental caries and oral health has been studied with inconclusive results. The objectives of this study were to determine the prevalence of, and the association between digit sucking, caries and oral hygiene status of children age six months to 12 years, resident in Ile-Ife, Osun State, Nigeria. METHODS: A cross-sectional study was conducted in Ife Central Local Government Area of Osun State. Data were collected through a household survey using a multi-stage sampling procedure from children between six months and 12 years. Details of each child’s socio-demographic characteristics, digit sucking habits, caries status and oral health status were collected. The association between digit sucking, caries status and oral hygiene status was determined using Chi square and Logistic regression. RESULTS: The mean age of the 992 study participants was 5.8 ± (3.2) years. The prevalence of digit sucking, caries and poor oral hygiene were 7.2%, 10.5% and 2.4% respectively. The mean dmft score was 0.22 ± (0.80), mean DMFT score was 0.04 ± (0.30) while mean Oral Hygiene Index score was 1.27 ± (0.73). Digit sucking increased the odds of having caries (OR: 1.28; CI: 0.58–2.81) but decreased the odds of having poor oral hygiene (OR: 0.58; CI: 0.34–1.01) insignificantly. CONCLUSIONS: Digit sucking was not a significant predictor of caries and oral hygiene status, although the odds of having caries increased while the odds of having poor oral hygiene decreased with digit sucking.